Nanotechnology for the treatment of allergic conjunctival diseases - Liu, Yu-Chi (2021)
Allergic conjunctivitis is one of the most common external eye diseases and the prevalence has been increasing. The mainstay of treatment is topical eye drops. However, low bioavailability, low ocular drug penetration, transient resident time on the ocular surface due to tear turnover, frequent topical applications and dependence on patient compliance, are the main drawbacks associated with topical administration. Nanotechnology-based medicine has emerged to circumvent these limitations, by encapsulating the drugs and preventing them from degradation and therefore providing sustained and controlled release. Using a nanotechnology-based approach to load the drug is particularly useful for the delivery of hydrophobic drugs such as immunomodulatory agents, which are commonly used in allergic conjunctival diseases. In this review, different nanotechnology-based drug delivery systems, including nanoemulsions, liposomes, nanomicelles, nanosuspension, polymeric and lipid nanoparticles, and their potential ophthalmic applications, as well as advantages and disadvantages, are discussed. We also summarize the results of present studies on the loading of immunomodulators or nonsteroidal anti-inflammatory drugs to nano-scaled drug delivery systems. For future potential clinical use, research should focus on the optimization of drug delivery designs that provide adequate and effective doses with safe and satisfactory pharmacokinetic and pharmaco-toxic profiles.